Use of Drugs with Anticholinergic Properties among Nursing Home Residents with Dementia: A National Analysis of Medicare Beneficiaries 2007-2008 - Palmer, Jacqueline B. (Drugs Aging, 2015)
BACKGROUND: Older adults with dementia are vulnerable to the central deteriorating effects of drugs with anticholinergic properties (DAP). These effects include falls and confusion and may exacerbate dementia-related symptoms. Many individuals with dementia also receive acetylcholinesterase inhibitors (AChEI), indicated for mild to moderate Alzheimer's disease. AChEI have opposing effects to DAP and consequently, concomitant use of DAP and AChEI may further impair cognition among patients with dementia. OBJECTIVES: Our objectives were to 1) evaluate the anticholinergic burden among nursing home (NH) residents with dementia; 2) characterize trends in use of DAP and concomitant use of DAP and AChEI among NH residents with dementia; and 3) identify factors associated with the use of DAP and concomitant use of DAP and AChEI. METHODS: We conducted a retrospective analysis of Medicare data from 2007-2008 linked to the Minimum Data Set. RESULTS: During the study period, 53,805 (77%) NH residents with dementia used at least one DAP each month. Sixty-seven percent of residents with dementia used Anticholinergic Burden Scale (ACBS) level 1 DAPs, 3% used level 2 and 31% used level 3 DAP. Thirteen percent of NH residents with dementia concomitantly used ACBS levels 2 or3 DAPs and AChEI. CONCLUSIONS: This study sheds new light on the prevalence of DAP use and concomitant use of DAP and AChEI among NH residents with dementia. Clinicians should consider alternatives with lower anticholinergic effects, particularly in patients already taking DAP.